Following nerve injury neuregulin-1 drives microglial proliferation and neuropathic pain via the MEK/ERK pathway. - Calvo, M; Zhu, N; Grist, J; Ma, Z; Loeb, J; Bennett, D (2011)
Following peripheral nerve injury microglia accumulate within the spinal cord and adopt a proinflammatory phenotype a process which contributes to the development of neuropathic pain. We have recently shown that neuregulin-1, a growth factor released following nerve injury, activates erbB 2, 3, and 4 receptors on microglia and stimulates proliferation, survival and chemotaxis of these cells. Here we studied the intracellular signaling pathways downstream of neuregulin-1-erbB activation in microglial cells. We found that neuregulin-1 in vitro induced phosphorylation of ERK1/2 and Akt without activating p38MAPK. Using specific kinase inhibitors we found that the mitogenic effect of neuregulin-1 on microglia was dependant on MEK/ERK1/2 pathway, the chemotactic effect was dependant on PI3K/Akt signaling and survival was dependant on both pathways. Intrathecal treatment with neuregulin-1 was associated with microgliosis and development of mechanical and cold pain related hypersensitivity which was dependant on ERK1/2 phosphorylation in microglia. Spinal nerve ligation results in a robust microgliosis and sustained ERK1/2 phosphorylation within these cells. This pathway is downstream of neuregulin-1/erbB signaling since its blockade resulted in a significant reduction in microglial ERK1/2 phosphorylation. Inhibition of the MEK/ERK1/2 pathway resulted in decreased spinal microgliosis and in reduced mechanical and cold hypersensitivity after peripheral nerve damage. We conclude that neuregulin-1 released after nerve injury activates microglial erbB receptors which consequently stimulates the MEK/ERK1/2 pathway that drives microglial proliferation and contributes to the development of neuropathic pain.